Wound Healing Activity of Pyrazole-thiazole Derivatives of Curcumin Through the Docking, Pharmacokinetics, MD Simulation and MM/GBSA Approaches - Forid, Md Shaekh; Roney, Miah; Uddin, Md. Nazim; Huq, A. K.M.Moyeenul; Mohd Hamzah, Mohd Nasir; Mohd Fadhlizil Fasihi, Mohd Aluwi; Muhammad Saupi, Azuri; Wan Maznah, Wan Ishak (International Scientific Organization, 2024)
Matrix metalloproteinase (MMP-2 and MMP-8) have been found to be promising targets for the discovery and development for of novel wound healing drugs candidate. However, there are currently no MMP-2 or MMP-8 inhibitors that are therapeutically helpful for treating wound healing. Therefore, the goal of this study was to investigate the wound healing potential of novel pyrazole-thiazole derivatives of curcumin using a series of computational studies. We first utilized the physicochemical and ADMET to screen the eight curcumin analogs and the outcomes from showed that compound C2 is potential favorable compound for further exploration. The docking analysis showed that compound C2 has strong binding affinity with the MMP-2 and MMP-8 compared to reference drug. Furthermore, MD simulation result indicated C2/MMP-2 complex is more stable than C2/MMP-8 complex. Likewise, MM/GBSA results suggest that binding stability of C2/MMP-2 complex is more stable as they showed most negative binding free energy (ΔGbind -24.434 kcal/mol) compared to C2/MMP-8 complex (ΔGbind -12.347). Furthermore, PCA and FEL analysis revealed that C2/MMP-2 complex displayed stable complex formation compared to C2/MMP8 complex in 100 ns molecular dynamics simulation trajectory. Hence, C2 could be considered a potent MMP-2 inhibitor and could be experimentally verified as a lead compound for the search for MMP-2 inhibitors for the treatment of wound healing.